Analisis Pengaruh Komunikasi Bisnis Efektif 7 C dan Strategi Promosi Model ISTEA Terhadap Peningkatan Penjualan - Ana Ramadhayanti (Universitas Bina Sarana Informatika, 2022)
Communication 7 C (X1), Promotion Strategy ISTEA Model (X2) and the dependent or dependent variable Sales Increase (Y). The purpose of this study was to determine the Effect of Effective Business Communication 7 C and ISTEA Model Promotion Strategy on Increasing Sales. The research method used is a comparatiave quantitative method, with research analysis using SPSS.25 calculations. The data processing used in SPSS is the result of distributing questionnaires to several samples. The results of the study using the t-test showed that the 7c effective business communication variable had a significant positive effect on increasing sales and the ISTEA Model Promotion Strategy variable had a significant positive effect on increasing sales. Meanwhile, using the f test simultaneously shows the results that there is an influence between Effective Business Communication 7 C and ISTEA Model Promotion Strategy on Sales Increase. The benefit of this research is to increase knowledge and insight to the public, especially regarding sales and promotional strategies.